Early Initiation of Breastfeeding Can Accelerate Uterine Involution in Postpartum Women - Epti Yorita; Juita Dian Anggraini; Sri Yanniarti; Rialike Burhan; Rina Rina (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Maternal Mortality Rate (MMR) in Indonesia is still high with the main causes of pre-eclampsia and postpartum hemorrhage, this occurs due to endometritis, congenital coagulation disorders as well as residual conception products, subinvolution of blood vessels at placental implantation. Therefore, efforts are needed to increase uterine contractions in the first minute after birth by stimulating the release of the hormone oxytocin so that the uterus contracts adequately with early initiation of breastfeeding (EIB). This study aims to determine the effect of EIB on uterine involution in postpartum mothers in Bengkulu Regency, Bengkulu Province. Design of research is cross sectional with independent variable of EIB, dependent variable of uterine involution. External variables measured include early mobilization, age and parity. The sample in this study were postpartum mothers on day 7, a total of 54 people selected by purposive sampling. The research site was located in Central Bengkulu Regency, Bengkulu Province. Data were analyzed univariate, bivariate with Mann Whitney and multivariate with ancova. There is an effect of EIB with uterine involution p=0.000. There is no relationship between parity and uterine involution p=0.100. There is a relationship between age and uterine involution p=0.00. There is a relationship between early mobilization and uterine involution p=0.00. EIB is the dominant factor affecting uterine involution in postpartum mothers. EIB is the dominant factor affecting uterine involution. Health care providers should perform EIB within the first hour after the birth of the baby to prevent sub involution in postpartum women. Keywords: Breastfeeding, Early, Initiation, Involution, Uterine